Differentiating authentic versus pseudo vulnerability in therapeutic practice1 - Simpson, Susan G.; Navot, Limor (Frontiers in Psychiatry, 2023)
The importance of empathy and attuned care as key ingredients in therapeutic healing has been widely recognised. However, empathy that is delivered in ways that are misaligned with the client’s clinical presentation and emotional states or ‘modes’ can have the opposite effect, reinforcing unhelpful coping patterns, and hindering recovery. In this theoretical development paper, it is proposed that ‘pseudo-vulnerability’ is an important yet overlooked source of therapeutic impasses, often resulting in unremitting clinical problems, and poor clinical outcomes. A range of commonly occurring pseudo-vulnerable presentations are described, including Complaining Protector, Attention/Recognition Seeking, and Self-Pity/Victim, with the addition of a new mode Helpless Surrenderer. Guidance on differentiating pseudo-vulnerable modes from each other and from the authentic Vulnerable Child mode are delineated, via characteristic clinical presentations and typical therapist countertransference reactions. Methods for managing pseudo-vulnerability to facilitate access to underlying authentic vulnerability are described.